DEFB1 gene 5' untranslated region (UTR) polymorphisms in inflammatory bowel diseases. - Zanin, Valentina; Segat, Ludovica; Bianco, Anna Monica; Padovan, Lara; Tavares, Nathalia de Alencar Cunha; Crovella, Sergio (Clinics (Sao Paulo), 2012)
Keywords: 5' Untranslated Regions; Adult; Antimicrobial Cationic Peptides; beta-Defensins; Case-Control Studies; Colitis, Ulcerative; Crohn Disease; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Inflammatory Bowel Diseases; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide

A real-time polymerase chain reaction-based protocol for low/medium-throughput Y-chromosome microdeletions analysis. - Segat, Ludovica; Padovan, Lara; Doc, Darja; Petix, Vincenzo; Morgutti, Marcello; Crovella, Sergio; Ricci, Giuseppe (Genet Test Mol Biomarkers, 2012)
PURPOSE: We describe a real-time polymerase chain reaction (PCR) protocol based on the fluorescent molecule SYBR Green chemistry, for a low- to medium-throughput analysis of Y-chromosome microdeletions, optimized according to the European guidelines and aimed at making the protocol faster, avoiding post-PCR processing, and simplifying the results interpretation. METHODS: We screened 156 men from the Assisted Reproduction Unit, Department of Obstetrics and Gynecology, Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy), 150 not presenting Y-chromosome microdeletion, and 6 with microdeletions in different azoospermic factor (AZF) regions. For each sample, the Zinc finger Y-chromosomal protein (ZFY), sex-determining region Y (SRY), sY84, sY86, sY127, sY134, sY254, and sY255 loci were analyzed by performing one reaction for each locus. RESULTS: AZF microdeletions were successfully detected in six individuals, confirming the results obtained with commercial kits. CONCLUSION: Our real-time PCR protocol proved to be a rapid, safe, and relatively cheap method that was suitable for a low- to medium-throughput diagnosis of Y-chromosome microdeletion, which allows an analysis of approximately 10 samples (with the addition of positive and negative controls) in a 96-well plate format, or approximately 46 samples in a 384-well plate for all markers simultaneously, in less than 2 h without the need of post-PCR manipulation.
Keywords: Azoospermia; Chromosome Deletion; Chromosomes, Human, Y; Female; Humans; Kruppel-Like Transcription Factors; Male; Real-Time Polymerase Chain Reaction; Sex Chromosome Aberrations; Sex Chromosome Disorders of Sex Development

A polymorphism in PRF1 gene is associated with HIV-1 vertical transmission in Brazilian children. - Padovan, Lara; Segat, Ludovica; Crovella, Sergio (AIDS, 2011)
We investigated the possible association between PRF1 gene polymorphisms and HIV-1 vertical transmission in Brazilian children by analyzing PRF1 gene coding and untranslated regions in 173 perinatally infected children (HIV+), 51 exposed uninfected (HIV-), and 171 HIV-unexposed uninfected children. Seven single nucleotide polymorphisms were identified in our samples. The rs885822 C allele and CC genotype were significantly more frequent in HIV-negative than in HIV-positive patients and associated with a protective effect toward HIV vertical transmission.
Keywords: Brazil; Female; HIV Infections; HIV-1; Humans; Infant, Newborn; Infectious Disease Transmission, Vertical; Male; Polymorphism, Genetic; Pore Forming Cytotoxic Proteins; Pregnancy

Histatins in non-human primates: gene variations and functional effects. - Padovan, Lara; Segat, Ludovica; Pontillo, Alessandra; Antcheva, Nikolinka; Tossi, Alessandro; Crovella, Sergio (Protein Pept Lett, 2010)
Human histatins are histidine-rich, low molecular weight salivary proteins that contribute to the immune system of the oral cavity. In this work, nucleotide sequences of the HIS1 (coding for histatin 1) and HIS2 (coding for histatin 3) genes, homologous to the human ones, have been sequenced and analysed in five primates species including Great Ape, Hylobatidae and Cercopithecidae. In HIS1, the region corresponding to the putative mature peptide shows a premature stop codon in Macaca and Cercopithecus, while HIS2 a six codon insertion in the Cercopithecidae. Histatin 5, a 24-residue peptide derived from histatin 3, is the most antimicrobially active among human histatins, thus macaque and nomascus orthologues of histatin 5 were selected for chemical synthesis and functional characterization, in comparison to the human peptide. All synthesized histatins are predicted to be poorly amphipathic, depending on the charged state of His residues and assume partially a-helical conformations only in lipophilic conditions. Antimicrobial assays against Candida and Criptococcus spp. indicate somewhat different spectra of in vitro activity against the tested fungi. We have described HIS1 and HIS2 gene variations in primates and have analysed their functional effects on selected Hst5 orthologues. The human antimicrobial peptide has been proposed to represent an important lead for new generation of antimicrobial compounds for the treatment of oral mycoses, thus the information from the non-human primates histatins studied may aid strategies for drugs design.
Keywords: Amino Acid Sequence; Animals; Anti-Infective Agents; Base Sequence; Candida; Catarrhini; Cell Proliferation; Computational Biology; Cryptococcus; Genetic Variation; Histatins; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

Structural aspects of plant antimicrobial peptides. - Padovan, Lara; Scocchi, Marco; Tossi, Alessandro (Curr Protein Pept Sci, 2010)
Antimicrobial peptides exert an important role in plant defence and their structure/activity relationship against pathogens is widely described. Although the most striking feature of these antimicrobial peptides is their molecular diversity, they share some common features, such as a relatively low molecular weight, and the presence of a variable number of cysteines residues that contribute to stabilize conserved scaffolds through disulphide bond formation, and can be assigned to different structural classes. Peptides from different classes in some cases act synergistically against pathogens when produced by the same tissue, and contribute to extending defence to a wider range of microbes. In this review we briefly describe the structure of some of the main plant antimicrobial peptide classes: thionins, defensins, lipid transfer proteins, cyclotides and snakins, and how they are reported to contribute to the plant protection. In many cases these antimicrobial peptides show a wider activity spectrum than that suggested by their name, exerting an action also against predatory insects and revealing useful antiviral activities. This extends their interest from defense of important food crops also to the design of novel anti-infective compounds for both pharmaceutical and agricultural applications.
Keywords: Amino Acid Sequence; Antimicrobial Cationic Peptides; Molecular Sequence Data; Plant Proteins; Plants; Sequence Alignment